Teller Motivation and Ethical Dilemmas: An Interpretative Phenomenological Analysis of Whistleblowing in the Banking Industry - Andi Nurrahma Gaffar; Alimuddin; Syarifuddin (LP2M IAIN Palopo, 2026)
Bank tellers face a high risk of fraud because they deal directly with physical cash, both as possible offenders and as bystanders to fraud. This study aims to dig into the motivation and ethical dilemmas of tellers using an interpretative phenomenological analysis of whistleblowing in the banking industry. This study uses a qualitative approach with the Interpretative Phenomenological Analysis (IPA) method developed by Jonathan A. Smith (1996). For participants and sampling, the study used purposive sampling to select an informant based on set criteria. There was one informant, namely a person who once worked as a teller at a private bank in South Sulawesi and had acted as a whistleblower. This case is highly unique and rare, and it forms a single case IPA study. For data collection and analysis, the data were gathered through semi-structured in-depth interviews This study produced four conclusions, among them that whistleblowing motivation among bank tellers is multidimensional and cannot be reduced to a single motive. Second, religiosity and transcendental values play a crucial role in resolving ethical dilemmas. Third, psychological resilience that is shaped by a sociocultural background, combined with the belief that sustenance is arranged by God, was shown to effectively moderate the perceived risk of retaliation, so that the threat of institutional sanctions did not become a real barrier to the decision to report. Fourth, formal control mechanisms such as dual control and dual custody, although important, are not enough to prevent fraud committed by individuals with high authority and planned intent.